BARMAN, Roderick J. Princess Isabel of Brazil: Gender and Power in the Nineteenth Century. - Daibert Junior, Robert (Revista Estudos Feministas, 2003)
BARMAN, Roderick J. Princess Isabel of Brazil: Gender and Power in the Nineteenth Century.